2017
DOI: 10.1089/neu.2015.4310
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Low-Pressure Blast-Wave Exposure Causes Distinct Behavioral and Morphological Responses Modelling Mild Traumatic Brain Injury, Post-Traumatic Stress Disorder, and Comorbid Mild Traumatic Brain Injury–Post-Traumatic Stress Disorder

Abstract: The intense focus in the clinical literature on the mental and neurocognitive sequelae of explosive blast-wave exposure, especially when comorbid with post-traumatic stress-related disorders (PTSD) is justified, and warrants the design of translationally valid animal studies to provide valid complementary basic data. We employed a controlled experimental blast-wave paradigm in which unanesthetized animals were exposed to visual, auditory, olfactory, and tactile effects of an explosive blast-wave produced by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
37
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 62 publications
8
37
1
Order By: Relevance
“…The overpressure wave is followed with a negative pressure wave that is sustained for more than 0.66 ms with a peak negative pressure of −40 kPa (−5.8 psi). This blast protocol is reported to result in a sound pressure level of 193 dB and a light intensity of approximately 5 Mlux (Zuckerman et al 2016), which is similar to that experienced during exposure to a M84 stun grenade at a distance of 1.5 m (3.1 Mlux). The peak overpressure deviations between the different experimental trials were between 1 and 3%.…”
Section: Methodsmentioning
confidence: 68%
See 4 more Smart Citations
“…The overpressure wave is followed with a negative pressure wave that is sustained for more than 0.66 ms with a peak negative pressure of −40 kPa (−5.8 psi). This blast protocol is reported to result in a sound pressure level of 193 dB and a light intensity of approximately 5 Mlux (Zuckerman et al 2016), which is similar to that experienced during exposure to a M84 stun grenade at a distance of 1.5 m (3.1 Mlux). The peak overpressure deviations between the different experimental trials were between 1 and 3%.…”
Section: Methodsmentioning
confidence: 68%
“…Non-anesthetized rats were subjected to a single blast wave with the head facing the blast without any body shielding, resulting in a full body exposure to the blast wave. Previous research has reported that this low-pressure blast wave results in a mean peak overpressure of 95 kPa (13.77 psi) (rise time of 0.01 ms) that is sustained for a duration of 0.19 ms and leads to a peak impulse of 10.8 × 10 −3  kPa s −1 (Zuckerman et al 2016). The overpressure wave is followed with a negative pressure wave that is sustained for more than 0.66 ms with a peak negative pressure of −40 kPa (−5.8 psi).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations